'The Feast of the Ants': Agency, the Body, and Qur'anic Narrative in Hisham Matar's In the Country of Men. Issue 3 (October 2014) - Hashem, Noor
<x xml:space="preserve">Abstract</x> Representations of the Qur'an in English fiction conventionally focus on the text as having problematic agency; when read, it inhibits the passive reader through commandments that prompt violence and interfere with personal freedoms and human rights. Recuperative texts focus instead on the Qur'an's affirmative spiritual aspects. Rather than flipping the dichotomy of the active agent/passive object, what if the relationship between narrative and reader subjectivity is seriously reconsidered? Hisham Matar's In the Country of Men explores the situations in which narratives – including those in the Qur'an – are made to be authoritative and effective. The Qur'anic story of Solomon and the ants resonates throughout a novel in which the narrator, Suleiman, learns to differentiate between the legitimate uses of narrative and the discourse of power abused by a corrupt Libyan government and a patriarchal society. It explores the slippages between networks of agencies that are prefigured in Suleiman's childhood narratives, narratives which later limit his ability to have a constructive bodily experience. How does this approach complicate the anthropocentric privileging of singular agency? What are the situations in which texts are authorised to be determinate and infectious while the reader is rendered passive, and which are those situations in which the individual asserts an interpretive agency over the text? How does this illustrate, in Talal Asad's terms, the 'phenomenal and conceptual' spaces 'whose limits are variously imposed, transgressed, and reset'? What role do these narratives play on the material body – as Saba Mahmood asks, what are 'the affective and embodied practices' prompted by 'attachment and cohabitation' to these narratives? Finally, what insight does this approach to Qur'anic narratives map out for the reading of non-religious texts?